Mergan Pharmaceutical’s Customer-Driven Flight into the Future - Chatterjee, Subroto (Indian Journal of Marketing, 2010)
S.S. Kutty walked rapidly down the corridor toward the president’s office of Mergan Pharmaceutical’s at Parel, Mumbai. He had been summoned there, pronto. It must be another crisis at the hub, he thought. His head was in a swirl. Kutty was soon going to take charge as deputy general manager (supply chain), but was only a couple of years away from retirement. He had just returned back to his Mumbai office from a three-day training program held at their Ahmedabad (Gujarat) office on "Customer Focus and Customer Satisfaction."